Optimasi Rute Pengisian Daya Kendaraan Listrik SPKLU Jakarta Pusat Menggunakan Dynamic Programming: Optimizing Electric Vehicle Charging Routes at Central Jakarta's SPKLU Using Dynamic Programming - Femmy Johan; Jennifer Verty; Yohannes Yohannes (Politeknik Negeri Malang, 2026)
The development of electric vehicles in Indonesia has increased the need for Public Electric Vehicle Charging Stations (SPKLU). Electric vehicle users often experience difficulties in determining the closest SPKLU location and in accordance with the current vehicle position. This study aims to create an optimization program for determining electric vehicle charging routes at SPKLU in the Central Jakarta area using the Dynamic Programming algorithm. Research data was obtained from Google Maps, including the SPKLU name, latitude, longitude, wattage, charger type, and address. Distance calculations were carried out using the Geodesic Distance method based on the coordinates of the vehicle and SPKLU locations. Next, reachable SPKLUs were evaluated using a cost function that combines travel distance and estimated charging time. The Dynamic Programming algorithm was used to determine the minimum cost value as the optimal solution, then the program generated a ranking of the best SPKLU recommendations. The study was built using the Python programming language and displayed visualizations of locations and routes to SPKLUs on a digital map using Folium. The results showed that the program was able to provide optimal SPKLU recommendations based on a combination of distance and charging time, thus helping electric vehicle users determine charging locations more effectively and efficiently.